Danny, the champion of the world - Dahl, Roald; Bennett, Jill (New York : Knopf : Distributed by Random House, 1975)
A young English boy describes his relationship with his father and the special adventure they share together.
Elem. School Library Collection.
Library Journal.
Booklist.
5.0
3-6
770L
Keywords: Fathers and sons -- Fiction; Father-son relationship -- Fiction; Fathers and sons -- Fiction